Crabs & Mollusks - Lewis, Brenda Ralph (Milwaukee, WI Gareth Stevens, 2006)
Feaatures crustaceans and shellfish from around the world, including the hermit crab, giant octopus, and spiny lobster.
Elementary
Keywords: Crabs; Mollusks; Octopus; Squid